Surface plasmon resonance sensing detection of mercury and lead ions based on conducting polymer composite - Abdi, Mahnaz M.; Abdullah, Luqman Chuah; Sadrolhosseini, Amir Reza; Mat Yunus, Wan Mahmood; Abd. Moksin, Mohd Maarof; Md. Tahir, Paridah (Public Library of Science, 2011)
A new sensing area for a sensor based on surface plasmon resonance (SPR) was fabricated to detect trace amounts of mercury and lead ions. The gold surface used for SPR measurements were modified with polypyrrole-chitosan (PPy-CHI) conducting polymer composite. The polymer layer was deposited on the gold surface by electrodeposition. This optical sensor was used for monitoring toxic metal ions with and without sensitivity enhancement by chitosan in water samples. The higher amounts of resonance angle unit (ΔRU) were obtained for PPy-CHI film due to a specific binding of chitosan with Pb2+ and Hg2+ ions. The Pb2+ ion bind to the polymer films most strongly, and the sensor was more sensitive to Pb2+ compared to Hg2+. The concentrations of ions in the parts per million range produced the changes in the SPR angle minimum in the region of 0.03 to 0.07. Data analysis was done by Matlab software using Fresnel formula for multilayer system.